2017
DOI: 10.1111/dom.13117
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of saxagliptin in combination with metformin as initial therapy in Chinese patients with type 2 diabetes: Results from the START study, a multicentre, randomized, double‐blind, active‐controlled, phase 3 trial

Abstract: Saxagliptin 5 mg plus metformin significantly improved glycaemic control compared with either monotherapy in treatment-naïve Chinese patients with type 2 diabetes, and was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
1
17
0
2
Order By: Relevance
“…The efficacy and safety of saxagliptin as monotherapy or combination therapy in Chinese patients with type 2 diabetes have been established in several studies 9‐12 . In the present study, saxagliptin as add‐on to metformin has shown consistent glycemic efficacy across a range of patient profiles.…”
Section: Discussionsupporting
confidence: 54%
“…The efficacy and safety of saxagliptin as monotherapy or combination therapy in Chinese patients with type 2 diabetes have been established in several studies 9‐12 . In the present study, saxagliptin as add‐on to metformin has shown consistent glycemic efficacy across a range of patient profiles.…”
Section: Discussionsupporting
confidence: 54%
“…We included 82 randomised controlled trials (fig 1) with 104 833 participants with type 2 diabetes in the traditional pairwise meta-analysis 343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115. Characteristics of studies and participants included in the pairwise meta-analysis are shown in table 1 and supplementary table C. The average age of participants was 59.4 years, and 39.7% (n=41 618) were female.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, db mice (12~16 weeks age) showed such a very high glucose state in severe diabetes that metformin did not recover blood glucose to normal level. Accordingly, the initial treatment dose at 10 mg/kg in db mice, equivalent of 600 mg/60 kg (commercially sold Diabex TM at a dose of 500 mg/kg/day or 1,000 mg/kg/day) ( 14 ) in men, might not be sufficient enough to lower the blood glucose level. Metformin is widely used as a hypoglycemic reagent for type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%